2017
DOI: 10.1073/pnas.1707513114
|View full text |Cite
|
Sign up to set email alerts
|

Organotypic models of type III interferon-mediated protection from Zika virus infections at the maternal–fetal interface

Abstract: Protecting the fetus from the hematogenous spread of viruses requires multifaceted layers of protection and relies heavily on trophoblasts, the fetal-derived cells that comprise the placental barrier. We showed previously that trophoblasts isolated from full-term placentas resist infection by diverse viruses, including Zika virus (ZIKV), and transfer this resistance to nonplacental cells through the activity of paracrine effectors, including the constitutive release of type III interferons (IFNs). Here, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 22 publications
13
100
0
Order By: Relevance
“…A recent report showed that third trimester primary human syncytialized trophoblasts were resistant to ZIKV infection, and conditioned medium from these cells protected against ZIKV infection, a property ascribed to the actions of constitutively released IFN-λ (Bayer et al, 2016). Consistent with this observation, first trimester syncytialized trophoblasts appear resistant to ZIKV infection (Bhatnagar et al, 2017; Ritter et al, 2017), and the syncytium in second trimester human explants constitutively release IFN-λ and do not support ZIKV infection (Corry et al, 2017). In comparison, first- and second-trimester cytotrophoblasts in cell culture are susceptible to ZIKV infection (El Costa et al, 2016; Weisblum et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…A recent report showed that third trimester primary human syncytialized trophoblasts were resistant to ZIKV infection, and conditioned medium from these cells protected against ZIKV infection, a property ascribed to the actions of constitutively released IFN-λ (Bayer et al, 2016). Consistent with this observation, first trimester syncytialized trophoblasts appear resistant to ZIKV infection (Bhatnagar et al, 2017; Ritter et al, 2017), and the syncytium in second trimester human explants constitutively release IFN-λ and do not support ZIKV infection (Corry et al, 2017). In comparison, first- and second-trimester cytotrophoblasts in cell culture are susceptible to ZIKV infection (El Costa et al, 2016; Weisblum et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…Routes of ZIKV vertical transmission could include infection of permissive extravillous trophoblasts (Tabata et al, 2016) and/or the maternal decidua, which would allow ZIKV to circumvent many of the most robust placental barrier functions, including those presented by syncytiotrophoblasts. In addition, primary human umbilical vein endothelial cells (HUVEC), uterine microvascular endothelial cells (hUtMEC), and primary full-term placental fibroblasts all are non-responsive to IFN-λ ((Fig S5) and (Corry et al, 2017)); cells that are non-responsive to IFN-λ could provide portals to facilitate ZIKV transplacental transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such clinical signs and behavioral abnormalities can be partially associated with altered glucocorticoid levels [7]. Zika virus also replicates in the placenta [8][9][10], a crucial player in cortisol traffic from mother to fetus in humans [11] and pigs [12]. Thus, we hypothesize that congenital ZIKV infection may affect in utero cortisol levels.…”
mentioning
confidence: 97%